“THERE IS NO PROPHET IN THE NATIVE COUNTRY”: TARAS SHEVCHENKO AND PATRIARCH YOSYF SLIPYI - Ivankovych, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates Patriarch Yosyf Slipyi’s reception of Taras Shevchenko’s creative work. On the basis of biographical data and priestly activities of the Cardinal of the Ukrainian Greek Catholic Church it proves the unity of thoughts and actions of the Ukrainian poet and the Ukrainian theologian for developing and self-affirming the national spirit of our statehood.